Empowerment of Karang Taruna in the Kali Gajah Wong Tourism Village through Increasing Literacy and Financial Inclusion - Christina Heti Tri Rahmawati; Ima Kristina Yulita; Firma Sulistiyowati; Aurelia Melinda Nisita Wardhani (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose This service activity raises the problems faced by the Kali Gajah Wong Tourism Village, where based on interviews with youth organizations as managers of the tourist village, so far the business financial management of this tourist destination has separated business and personal finances, but this has not been done regularly so it has not fulfilled the expected desires. from donors or the government who will increase capital. Therefore, financial management is important to develop this tourist destination. This mentoring activity aims to provide an understanding of financial literacy and inclusion so that tourist destination managers do not experience financial difficulties and can allocate income across various investment instruments. Methods - This activity was carried out using mentoring methods and continued sharing from the tourist village management. Result and discussions - The results of the assistance to the youth organization in the Kali Gajah Wong Tourism Village went smoothly and according to what had been planned, it went well and according to plan. The managers of this tourist village increasingly have a good understanding of financial literacy and inclusion and are able to separate personal and business finances, and can manage business finances more transparently. Conclusion – The implication of the results of this service activity is that it is hoped that tourist village managers can increase their understanding of financial literacy and inclusion so that they can improve business financial management and ultimately increase the income and welfare of the local community.